Progenitor cell therapy for neurological injury - Cox, Charles, S. (Stem Cell Biology and Regenerative Medicine, 2011)
There are currently no reparative therapies for severe neurological injury, including brain injury, spinal cord injury and stroke. Actually, most treatments are designed simply to limit secondary damage. However, pre-clinical data supports the idea that exogenous stem and progenitor cells have the potential to promote a reparative response to severe neurological injuries. Progenitor Cell Therapy for Neurological Injury is a compilation of seminal essays that explore many unique aspects of neurological injury, focusing on the critical translational issues of cell delivery. Specifically, it discusses routes of administration, types of progenitor cells (alone and/or in combinations), timing of delivery and adjuncts to promote cell engraftment, survival and effectiveness. In addition, many chapters address measuring the effects of transplanted cells and cell tracking. The paradigms of how cell-based therapeutics affect neurological injury is changing rapidly. The developments in this field may ultimately offer realistic hope for improvement in patients with severe injuries. This book is a vital key toward unlocking those future treatments.